Pengaruh Strategi POINT terhadap Kemampuan Membaca Pemahaman Siswa Kelas VIII SMPN 3 Talamau - Daniati, Eliza; Basri, Irfani; Nursaid, Nursaid (Universitas Negeri Padang, 2012)
Specifically, purposes of the research were: (1) to describe the ability of eighth grade student’s of SMP Negeri 3 Talamau in reading comprehension without using the point strategy technique, (2) to describe the ability of eighth grade student’s of SMP Negeri 3 Talamau in reading comprehension by using the point strategy technique, (3) to analyze the effectives of the point strategy technique in to the ability of eighth grade student’s of SMP Negeri 3 Talamau in reading comprehension. The type of the research was quantitative research by using experimental method. Research findings provides that learning by using strategy point in experimental classroom was effective with average 70,4 in qualification more than enough. In contrast, control class in average 63,7 in qualification enough.